Left obturator hernia, intestinal obstruction and bilateral inguinal hernia: a case report - Leon-Cabrera, Zamiara (2023)
Obturator hernia has an incidence of less than 1% of all abdominal wall hernias, it is predominantly observed in elder women and it is characterized by protrusion of intra-abdominal viscera into the shutter hole. The preoperative diagnosis is difficult due to the lack of external manifestations, nonspecific symptoms and lack of clinical suspicion. Delaying diagnosis and treatment is associated with high mortality. We report the case of a female patient with a complicated obturator hernia with concomitant bilateral inguinal hernias that underwent minimally invasive surgery with no complications and a seven day stay in hospital.